Regulasi Peraturan Daerah Kota Palangka Raya Nomor 09 Tahun 2012 dan dampaknya terhadap Badut Jalanan di Kota Palangka Raya - Muhamad Aidil; Meysarah Meysarah; Ahmad Rusdie Nur Fadillah; Muhammad Noor Aini; Muzalifah Muzalifah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Regional Regulation of Palangka Raya City Number 09 of 2012 focuses on regulating the use of public spaces and economic activities, including the presence of street clowns as an important element in the city's cultural diversity. Street clowns, who serve as both entertainment and a source of income, face significant challenges due to this regulation, especially regarding permits, locations, and operating hours. Although aimed at creating a neat and orderly urban environment, the implementation of regulations often does not consider the broader social impacts, thereby limiting their mobility and disrupting their income. This research analyzes the impact of Regional Regulation Number 09 of 2012 on the lives of street clowns, by exploring the provisions in the regulation and their responses to the challenges faced. The methods used include literature review and data analysis from previous research, regulatory documents, and related literature. The research results are expected to provide insights into the interaction between government regulations and the lives of the informal sector community, as well as to evaluate the balance between urban planning and the protection of street clowns' rights as an integral part of Palangka Raya's culture.